Fracture resistance of simulated immature teeth after different intra-radicular treatments - Sivieri-araujo, Gustavo (2015)
The aim of this study was to evaluate the fracture resistance of simulated immature teeth after different intra-radicular treatments. Crowns and roots of bovine incisors were cut transversally and removed to simulate immature teeth. Root canal preparation and flaring were performed using a bur in crown-apex and apex-crown direction. The samples were distributed into 5 groups (n=10): Positive control (PoC) - no root canal flaring or filling; Negative control (NeC) - teeth were sectioned and their root canals were flared; Direct anatomical glass fiber post (RaP) - #2 Reforpost main glass fiber post relined with composite resin; Double tapered conical glass fiber posts (ExP) - #3 Exacto glass fiber post; and #2 Reforpost main glass fiber + Reforpin accessory glass fiber posts (RrP). In RaP, ExP and RrP, 4.0-mm apical plugs were done with MTA Angelus. The specimens were embedded in polystyrene resin inside cylinders and the periodontal ligament was simulated with a polyether-based impression material. The specimens were submitted to compressive fracture strength test (0.5 mm/min at 135° relative to the long axis of the tooth) in a servo-hydraulic mechanical testing machine MTS 810. Data were subjected to one-way ANOVA and Dunnett's C or Tukey's tests (α=0.05). The control groups (PoC and NeC) showed lower fracture strength than the experimental groups. NeC presented the lowest resistance and ExP presented the highest resistance among the experimental groups. The flaring procedures produced a detrimental effect on the fracture resistance of the bovine teeth. Glass fiber intra-radicular posts increased significantly the fracture resistance of simulated immature teeth.